Midwifery practice: Concept Paper - Tshuma, Bongani; Kasu, Christine, Mary; Mugadza, Gladys (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Objectives: Midwifery practice is often not well understood. Midwifery practice is dynamicand varies in many countries. It ranges from preconception care, care given to women duringpregnancy, labour and delivery, and postpartum care to competencies expected of individualpractice. The objective of this paper was to clarify, explain and describe the concept ofMidwifery Practice.Methods: The concept analysis of Midwifery Practice was done using the eight steps ofWalker and Avant’s strategic method. Initially twenty-five (25) articles from year 2000 to2017 were reviewed. Six (6) articles were later dropped due to their irrelevant information,and nineteen (19) articles were finally reviewed to describe Midwifery Practice.Results: The main antecedents of Midwifery Practice were a Diploma in General Nursingand enrolment into a post-basic Diploma in Midwifery for one year. On successfulcompletion of the midwifery course, he/she registers with the nurse’s council to practice as amidwife. The attributes identified in literature for Midwifery Practice include the requisiteknowledge in midwifery, performance of the expected competencies, and having theauthority to practice as a midwife. The resultant consequences of Midwifery Practice includesupport, care and advice given to women during pregnancy, labour and post-partum period,and the care of the newborn. They also include reduction in maternal and neonatal morbidityand mortality, and job satisfaction. The empirical referents fundamental to MidwiferyPractice include ability to take complete history and perform a physical examination todiagnose risk factors, manage and refer appropriately. They also include conducting cleanand safe deliveries, and management of obstetric emergencies.Conclusion: Midwifery Practice may take several forms but should be in line withinternational standards as described by the International Confederation of Midwives. In viewof the important role played by midwives in the health delivery system, it is crucial for eachpractitioner to understand the scope of their practice. The midwife is recognised as aresponsible and accountable professional who works with and in partnership with women togive the necessary support, care and advice during pregnancy, labour and the post-partumperiod.